2019
DOI: 10.20473/bhsj.v2i2.14965
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Neopterin Levels and Outcome in 30 Day HIV/AIDS Naive Patients

Abstract: Introduction: HIV/AIDS is still a major problem throughout the world even in Indonesia. Some markers can provide information regarding the description of immune activity in HIV/AIDS. Neopterin produced by macrophages as a catabolic result of Guanosine Triphosphate (GTP) is one of them. Neopterin has been widely studied as a prognostic indicator of the course in HIV/AIDS. Until now there have been no studies examine the association between neopterin levels and outcomes in 30 days of HIV/AIDS patients.Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…10 The ARV is initiated in HIV patients without tuberculosis infection regardless of CD4 count. 13 First-line ARVs are given in combination of two nucleoside reverse-transcriptase inhibitors (NRTI), added with a nonnucleoside reverse-transcriptase inhibitor (NNRTI) or protease inhibitor (PI). 11 The treatment of FDC once a day consisting of tenofovir disoproxil fumarate, lamivudine and efavirenz is a combination that shows good therapeutic and virological response, rarely causes severe side effects and is the main choice of ARV in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The ARV is initiated in HIV patients without tuberculosis infection regardless of CD4 count. 13 First-line ARVs are given in combination of two nucleoside reverse-transcriptase inhibitors (NRTI), added with a nonnucleoside reverse-transcriptase inhibitor (NNRTI) or protease inhibitor (PI). 11 The treatment of FDC once a day consisting of tenofovir disoproxil fumarate, lamivudine and efavirenz is a combination that shows good therapeutic and virological response, rarely causes severe side effects and is the main choice of ARV in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have shown that prophylactic administration of cotrimoxazole (TMP-SMX) in patients with low CD4 count can reduce the risk of opportunistic infections and mortality. 10, 13 In this case, the patient was diagnosed with HIV stage III due to weight loss of 15 kg (>10%) in 3 months, oral candidiasis in the last one month, history of sexual intercourse with men, chronic respiratory and mucocutaneous infections, reactive results of the three methods of examination, had a CD4 count of 14 cells/ µL and a viral load of 1,582,851 copies/mL. Fixed dose combination of ARV therapy (tenofovir disoproxil fumarate, lamivudine and efavirenz) was given because there was no pulmonary tuberculosis comorbidity (GeneXpert negative) and other laboratory results were normal.…”
Section: Discussionmentioning
confidence: 99%